MERCOSUR : integration and industrial policy. - LEIPZIGER, Danny M. ([et al] (1997)
Presents the objectives and effects of Mercosur, and discusses the industrial policies of member states within the general framework of Mercosur. Issues guidelines for Mercosuer industrial policy oversight.